OLASAGARRE, Juanjo. Ezinezko maletak: Susa argitaletxea. Donostia, 204ko martxoa. 249 orrialde - Arozena, Ainhoa (EGAN, 2021)
AINHOA AROZENA. OLASAGARRE, Juanjo. Ezinezko maletak Susa argitaletxea. Donostia, 204ko martxoa. 249 orrialde